In-vivo imaging of blood–brain barrier permeability using positron emission tomography with 2-amino-[3-11C]isobutyric acid. Issue 12 (December 2015) - Okada, Maki; Kikuchi, Tatsuya; Okamura, Toshimitsu; Ikoma, Yoko; Tsuji, Atsushi B.; Wakizaka, Hidekatsu; Kamakura, Tomoo; Aoki, Ichio; Zhang, Ming-Rong; Kato, Koichi
Abstract : Objective: The blood–brain barrier (BBB) limits the entry of some therapeutics into the brain, resulting in reduced efficacy. BBB-opening techniques have been developed to enhance the entry into the brain. However, a noninvasive, highly sensitive and quantitative method for evaluating the changes in BBB permeability induced by such techniques is needed to optimize treatment protocols. We evaluated 2-amino-[3- 11 C]isobutyric acid ([3- 11 C]AIB) as a PET probe to quantify BBB permeability in model rats. Methods: BBB opening was induced by a lipopolysaccharide injection or focused ultrasound (FUS) sonication. [3- 11 C]AIB distribution in the brain was evaluated by autoradiography and PET and compared with that of Evans blue, a traditional BBB permeability marker. Kinetics of [3- 11 C]AIB was compared with that of gadolinium-diethylenetriamine pentaacetic acid (Gd-DTPA)-enhanced MRI. The unidirectional blood–brain transfer constant ( K i ) of [3- 11 C]AIB was estimated using the Patlak plot. Results: [3- 11 C]AIB uptake in the lesion area was significantly higher than that in the control area and radioactivity colocalized with Evans blue in both models. [3- 11 C]AIB uptake in the FUS-sonicated region decreased over time after sonication. The ratio of [3- 11 C]AIB accumulation in the FUS-treated to the contralateral side increased during the experimental period, whereas that of the Gd-DTPA intensity reached a maximum at 10 min after injection and decreased thereafter. The [3- 11 C]AIB K i values were significantly higher in the lesion area than the control area. Conclusion: [3- 11 C]AIB PET is a promising, highly sensitive and quantitative imaging method for assessment of BBB permeability.